Growth Performance of Galaxy Rasbora Danio margaritatus Larvae Maintained at Different Stocking Densities - Iskandar, Andri; Ramadhan, Rahma Zulfa; Dermawan, Budi (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
The issue of low survival rates and high mortality of larvae is commonly encountered during the rearing process. The success of larval rearing is significantly influenced by optimal stocking density, good water quality, and controlled feed management, all of which affect the growth and survival of the larvae. The aim of this applied research is to implement rearing techniques with different stocking densities and assess their effects on the growth and survival of galaxy rasbora (Danio margaritatus) larvae. This study employed a Completely Randomized Design (CRD) with four different stocking density treatments: 1 fish L⁻¹ for treatments KT1 and PT1, 2 fish L⁻¹ for treatment PT2, and 3 fish L⁻¹ for treatment PT3, each with three repetitions. The results showed that different stocking densities had a significant effect on the growth and survival of the larvae. The highest survival rate was observed in treatment PT2, with 96% survival. The control treatment (KT1), which used a semi-intensive system, achieved the highest absolute length growth of 6.87 mm and the highest daily length growth rate of 32.73% day⁻¹. The stocking density of 2 fish L⁻¹ in treatment PT2 demonstrated optimal results in terms of survival and growth.